Digital Marketing sebagai Solusi Pengembangan Usaha Kripik Gadung di Desa Made Jombang - Hidayat, Rohmat; Qomariyah, Siti Nur; Aziz, Abdul; Nurdiansyah, Achmad Irfan; Aprilia, Yayang Inggrit Putri; Mafaza, Arin Vina; Qotrunnada, Serliya; Ahmada, Mila; Ardiansyah, Nur Cahyo (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2025)
Digital marketing is a strategic approach that utilizes digital media and internet technology to promote products, services, or brands to specific target audiences. Its main objective is to achieve business goals such as increasing brand awareness, generating leads, and boosting sales through various digital platforms. This initiative aims to improve the digital marketing knowledge and skills of micro, small, and medium enterprises (UMKM) by using Shopee E-Commerce. The approach is designed to teach UMKM participants effective digital marketing techniques, equipping them with the ability to promote their products online. The community service project, under the PKM scheme, was conducted from mid-August to the end of August 2024. It included visits to the homes of UMKM members in Made Kudu Jombang Village. The program focused on digital marketing training and mentoring, utilizing Shopee E-Commerce as a platform. The method used was Participatory Action Research (PAR), which included problem identification, joint planning, action implementation, and reflection and evaluation. The results of the program led to two key conclusions: (1) The Made Village community began to understand the importance of digital marketing. It plays a crucial role in increasing market reach, enhancing brand visibility, and introducing local products to national and international markets, benefiting the growth of village UMKMs. (2) Digital marketing enables village UMKMs to reach a wider audience at a lower cost, opening up new opportunities for business expansion and growth.